NZEB, cost- and comfort-optimal retrofit solutions for an Italian Reference Hotel. (December 2017) - Buso, Tiziana; Becchio, Cristina; Corgnati, Stefano P.
Abstract: Building upon the implementation of EBPD recast in the large majority of EU Member States, this paper studied how far cost-optimality is from the Nearly Zero Energy Building (NZEB) performance level for an Italian Reference Hotel (RH) undergoing major renovations. The energy performances of retrofit options for the RH were compared with the Italian NZEB requirements. Simulations results confirmed that the Italian NZEB target is reachable. However, the financial analysis of these retrofit options denounced a worrying gap between financially interesting solutions and NZEB ones. Then, through a novel comfort-optimal approach, the comfort-related consequences of the proposed retrofit options were investigated.